Cut-off points for weight and body mass index adjusted bioimpedance analysis measurements of muscle mass - TUFAN ÇİNÇİN, ASLI (SPRINGER, 2019)
Low skeletal muscle mass (LMM) is a criterion to define both sarcopenia and malnutrition. Muscle mass varies with gender, height, weight or fat mass, and many indices of adjusted-muscle mass have been proposed. We aimed to find reference cut-off points of the skeletal muscle mass index (SMMI) adjusted for weight and body mass index (BMI) in Turkish population. Adults between 18 and 39 years of age and community-dwelling older adults of 60-99 years of age were included. Body composition was assessed with bioimpedance analysis (BIA). SMMI adjusted for weight and BMI were calculated [SMMI (weight) and SMMI (BMI)]. Muscle strength was assessed by hand-grip-strength with hand dynamometer. SMMI (weight) cut points were calculated from the healthy young adults' data as mean SMMI-2 standard deviation (SD). SMMI (BMI) cut points that predict low muscle strength were calculated with ROC analysis. To define low muscle strength, we used three currently suggested low muscle-strength thresholds, i.e., 32 kg/22 kg, 30 kg/20 kg, 26 kg/16 kg in males/females, respectively. 301 healthy young adults (187 male, 114 female) and 992 older people (308 male, 684 female) were included. LMM cut points for SMMI (weight) were 37.4% and 33.6% for males and females, respectively. SMMI (BMI) cut points that best predict the low grip-strength for 32 kg/22 kg; 30 kg/20 kg; 26 kg/16 kg thresholds were1.017 kg/BMI and 0.677 kg/BMI; 1.014 kg/BMI and 0.710 kg/BMI; 1.036 kg/BMI and 0.770 kg/BMI for males and females, respectively. Muscle-mass adjustment methods and techniques show diversity among the studies and have impact on the LMM cut-off points. This study presents population specific LMM thresholds for skeletal muscle mass adjusted for weight and BMI aiming to increase and improve the general applicability of the leading sarcopenia consensus definitions.
Keywords: Body mass index; Cut-off; Low muscle mass; Sarcopenia; Skeletal muscle mass index; Weight; ALTERNATIVE DEFINITIONS; FUNCTIONAL IMPAIRMENT; GRIP STRENGTH; OLDER MEN; SARCOPENIA; PREVALENCE; MOBILITY; CUTPOINTS; CRITERIA